2016
DOI: 10.5194/angeo-34-657-2016
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of AOD from 17 CMIP5 models based on satellite-derived AOD over India

Abstract: Abstract. Aerosol optical depth (AOD) values from 17 CMIP5 models are compared with Moderate Resolution Imaging Spectroradiometer (MODIS) and Multiangle Imaging Spectroradiometer (MISR) derived AODs over India. The objective is to identify the cases of successful AOD simulation by CMIP5 models, considering satellite-derived AOD as a benchmark. Six years of AOD data (2000)(2001)(2002)(2003)(2004)(2005) from MISR and MODIS are processed to create quality-assured gridded AOD maps over India, which are compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…The larger MODIS AOD compared to MISR over India has been reported in many previous studies (e.g. Misra et al [10], Ramachandran and Kedia [41], David et al [42]). We show that AOD climatologies from MISR are also more stable than those from MODIS over these two regions.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The larger MODIS AOD compared to MISR over India has been reported in many previous studies (e.g. Misra et al [10], Ramachandran and Kedia [41], David et al [42]). We show that AOD climatologies from MISR are also more stable than those from MODIS over these two regions.…”
Section: Discussionsupporting
confidence: 49%
“…Pan et al [4] used satellite-derived AOD averaged for the eight years between 2000 and 2007. The six-year mean AOD between 2000 and 2005 was compared with model simulations in Misra et al [10]. More recent studies define AOD climatologies as the mean of AOD over a longer period of time than 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Recent surface and aircraft measurements reported similar high CCN concentration (2,000–6,000/cm 3 ) within the boundary layer during monsoon season over the GB (Bhattu & Tripathi, ; Dumka et al, ; Roy et al, ; Sarangi et al, ; Srivastava et al, ). Moreover, satellite observations and global modeling studies indicated similar spatial differences in aerosol loading over North India during monsoon season (Misra et al, , and references therein). Thus, this methodology of prescribing CCN emission fluxes as surface source in each grid box and allowing them to physically move around with the meteorological forcing is able to mimic reasonably well the spatial and vertical distribution of CCN over North India.…”
Section: Data Set and Model Detailsmentioning
confidence: 79%
“…The influences of anthropogenic land use and land cover change are also not included in the regression model. Anthropogenic land use and land cover change has been found to play an important role in long-term dust variability in some regions (e.g., Neff et al, 2005Neff et al, , 2008Moulin and Chiapello, 2006;McConnell et al, 2007), although previous modeling studies found its influences on future dust emissions to be minor compared to climate change . Thus the projection made by the regression model Figure 9.…”
Section: Regionmentioning
confidence: 99%
“…They found most CMIP5 models, except two HadGEM2 models, underestimated dust load over the Indo-Gangetic Plains and suggested the biases are due to a misrepresentation of 850 hPa winds in the models. Later, Misra et al (2016) also examined CMIP5-modeled AOD for India but did not specifically focus on dust. Shindell et al (2013) examined the output of 10 models from the Atmospheric Chemistry and Climate Model Intercomparison Project (ACCMIP) for 1 year 2000, among which eight models also participated in the CMIP5.…”
Section: Introductionmentioning
confidence: 99%